2013
DOI: 10.1073/pnas.1218721110
|View full text |Cite
|
Sign up to set email alerts
|

Direct production of mouse disease models by embryo microinjection of TALENs and oligodeoxynucleotides

Abstract: The study of genetic disease mechanisms relies mostly on targeted mouse mutants that are derived from engineered embryonic stem (ES) cells. Nevertheless, the establishment of mutant ES cells is laborious and time-consuming, restricting the study of the increasing number of human disease mutations discovered by highthroughput genomic analysis. Here, we present an advanced approach for the production of mouse disease models by microinjection of transcription activator-like effector nucleases (TALENs) and synthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
128
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(134 citation statements)
references
References 28 publications
6
128
0
Order By: Relevance
“…We observed TALEN-mediated induction of NHEJ in 25.4% of the offspring independent of targeting construct integration. These results are in line with efficiencies reported for zinc-finger nucleases in mice [25][26][27] and rats 28 , as well as for TALEN-injections in murine oocytes 6,12,13,29 . Newly established methodology using the CRISPR/Cas9 system to induce DNA double-strand breaks and facilitate homologous recombination 21,22 certainly raises high expectations that this system could also be used to mediate homologous recombination of larger donor plasmids directly in oocytes 22 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We observed TALEN-mediated induction of NHEJ in 25.4% of the offspring independent of targeting construct integration. These results are in line with efficiencies reported for zinc-finger nucleases in mice [25][26][27] and rats 28 , as well as for TALEN-injections in murine oocytes 6,12,13,29 . Newly established methodology using the CRISPR/Cas9 system to induce DNA double-strand breaks and facilitate homologous recombination 21,22 certainly raises high expectations that this system could also be used to mediate homologous recombination of larger donor plasmids directly in oocytes 22 .…”
Section: Discussionsupporting
confidence: 90%
“…11). While this manuscript was in preparation such findings have been extended to the mouse using a similar strategy for homologous recombination in mice that utilizes either short ssDNA donor templates or donor vectors to correct a single base mutation 12,13 . This work demonstrated that a donor vector with long homology regions, similar to the one used for this study, can be used for homology-directed repair in oocytes to exchange single base mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, indels introduced by NHEJ are variable in size and sequence, which make screening for functionally disrupted clones arduous (15) and do not allow for precise alterations. TALEN-or CRISPR/ cas9-mediated homology-directed repair (HDR) supports the introduction of defined nucleotide changes; however, so far this has only been demonstrated in lower eukaryotic models, including yeast (19), zebrafish (20), and, very recently, mice (21,22).…”
mentioning
confidence: 99%
“…For the expression of TALENs in mammalian cells we used the expression vector pCAG-TALEN-pA as described in Wefers et al (2013). pT7-TALEN-95A was derived from pCAG-TALEN-pA by replacementof the poly(A) signal sequence with a segment of 95 adenine residues derived from a mouse Oct4 cDNA clone. …”
mentioning
confidence: 99%